Make A Match Learning Model Assisted with Picture Media Improve Students’ Reading Skills - Yuliawati, Ni Putu Feny; Rati, Ni Wayan; Suranata, Kadek (Universitas Pendidikan Ganesha, 2020)
The results reading skills of students in grade II is relatively low. That is due to the high activity of students who tend to like to play and have not applied the relevant learning method. Therefore, this study aims to analyze the effect and differences in students' reading skills resulting from the application of the Make a Match type of cooperative learning model assisted by picture media. The type of this study is pre-experimental research with a Static Group Comparison design. The study population was 98 students while the sample of this study was 39 students taken by the selection of all the population in each class as an intact group randomly. The data of the students reading skills were obtained using the non-test method (observation). Data were analyzed using descriptive statistics, inferential statistics (t-test), and Cohen's test. Based on the results of hypothesis testing obtained from the results of research on students 'reading difficulties (t-count = 14.60> t-table = 1.69 at a significance level of 5%), and there is a Make A Match type cooperative learning model that is assisted by image media to test students' reading skills (d = 4.91> 0.8), thus it can be concluded that the cooperative learning model of the type of Make A Match aided by media images has a positive effect on students' reading skills.